TRANSFORMASI TRADISI MACCELLENG-CELLENG DI TENGAH MODERNISASI: LITERATURE REVIEW TENTANG ADAPTASI RITUAL DAN RESILIENSI BUDAYA BUGIS PANGKEP - Indriani; M. Ridwan Said Ahmad; Hudayah Sulaiman; Ramdani Sidik; Muhammad Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Maccelleng-celleng is a traditional component of Bugis marriage ceremonies in Pangkep Regency, conducted on the night preceding the wedding. The tradition involves a visit by the groom’s extended family to the bride’s residence, a family convoy, a door-opening ritual, and the throwing and catching of snacks or household necessities. Modernization, changing family relations, technological development, and the growing influence of religious rationality have affected both the form and meaning of this tradition. This article examines the transformation of Maccelleng-celleng, the cultural elements that remain preserved, and the adaptive mechanisms supporting its continuity. The study employed an integrative literature review of publications addressing Maccelleng-celleng, Bugis marriage practices, ritual transformation, modernization, and cultural resilience. The literature was analyzed through thematic identification, comparison, interpretation, and conceptual synthesis. The review identifies four major transformations: a functional shift from verifying the bride’s presence to celebrating social togetherness, the replacement of ritual objects with modern consumer goods, negotiation between customary practices and Islamic norms, and an increasing need for digital documentation and intergenerational transmission. Despite changes in its outward form, Maccelleng-celleng continues to function as a means of connecting families, reinforcing solidarity, expressing collective happiness, and affirming Bugis cultural identity in Pangkep. Modernization therefore does not simply eliminate tradition. Instead, it encourages communities to select, reinterpret, and contextualize inherited practices. The sustainability of Maccelleng-celleng depends on the community’s capacity to preserve its central meanings while adapting its modes of performance to contemporary social, religious, and technological conditions.